Assessment of Needs for Developing Curriculum Study Program for Masters of Education in Madrasah Ibtidaiyah Teachers Towards Excellent Accreditation - Samsul Susilawati; Muhamad Zubad Nurul Yaqin; Wahidmurni Wahidmurni; Candra Avista Putri (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2023)
This research was conducted to find out how the curriculum development design for the Madrasah Ibtidaiyah Masters of Teacher Education Study program led to superior accreditation, how to implement the curriculum for the Madrasah Ibtidaiyah Masters of Teacher Education Study program towards superior accreditation, as well as the learning outcomes in the Madrasah Ibtidaiyah Masters of Teacher Education study program. This research is a mixed research with a sequential explanatory research approach. The result of this research is that the curriculum development design for the Madrasah Ibtidaiyah Masters of Education (MPGMI) study program towards superior accreditation is carried out by conducting a continuous review of the MPGMI Study Program curriculum to obtain input for curriculum improvements that are being implemented. Implementation of the Madrasah Ibtidaiyah Teacher Education Master's Study Program Curriculum Towards Superior Accreditation is presented in the form of the MPGMI Study Program Curriculum Structure, MPGMI Study Program Activities and Prospects, MPGMI Study Program HR, Supporting Educational Facilities and Infrastructure. Learning Outcome Achievements in the Madrasah Ibtidaiyah Teacher Education Masters Study Program can be seen from the progress of alumni and the results of student publications.